2007
DOI: 10.1196/annals.1422.057
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of an Inhibitor of Nuclear Factor‐Kappa B on Thrombogenic Properties of Antiphospholipid Antibodies

Abstract: It has been shown that endothelial cell (EC) activation and tissue factor (TF) upregulation in EC and monocytes by antiphospholipid antibodies (aPL Abs) leads to a prothrombotic state and involves translocation of nuclear factor-kappa B (NF-kappaB). Here we examined the effects of an NF-kappaB inhibitor on aPL-induced thrombosis, TF activity, and EC in vivo. We treated CD1 mice with IgG from a patient with antiphospholipid syndrome (IgG-APS) or with control IgG (IgG-NHS). The adhesion of leukocytes (number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 52 publications
2
44
1
1
Order By: Relevance
“…20 Thus, modulation of NF-B activity may provide an opportunity to reverse the pathologic vascular response in APS. The Krüppel-like factors (KLFs), 21 particularly KLF2 and KLF4, inhibit inflammatory cytokinemediated responses in endothelial cells, 22,23 at least in part through inhibition of NF-B activity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Thus, modulation of NF-B activity may provide an opportunity to reverse the pathologic vascular response in APS. The Krüppel-like factors (KLFs), 21 particularly KLF2 and KLF4, inhibit inflammatory cytokinemediated responses in endothelial cells, 22,23 at least in part through inhibition of NF-B activity.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the MAPK pathway and NF-kB is an essential late step in TLR4 signal transduction pathways. Several research groups working independently have shown the integral role for p38MAPK and NF-jB in the transduction cascade of aPLinduced cell activation (Dunoyer-Geindre et al, 2002;Bohgaki et al, 2004;Simoncini et al, 2005;Sorice et al, 2007), while there is both in vitro and in vivo evidence that direct inhibitors of the two transcription factors interfere with aPL-induced pathogenesis (Montiel-Manzano et al, 2007;Vega-Ostertag et al, 2007). Therefore, inhibitors of NF-jB and p38MAPK may be a worthwhile approach in the APS setting.…”
Section: Potential Immunomodulatory Approaches In Apsmentioning
confidence: 99%
“…Pierangeli et al In summary, these animal models of thrombosis and endothelial cell activation have not only been useful in demonstrating the pathogenic effects of aPL antibodies and their causative role in inducing APS morbidity, but have also been instrumental in dissecting the intracellular mechanisms involved, in identifying cellular receptors activated by aPL antibodies in vivo and in testing potential new treatments for APS (discussed in detail in other sections of this chapter) [37,39,51,[93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: A Animal Models Of Thrombosis and Endothelial Cell Activationmentioning
confidence: 99%
“…Most of these have been discussed in other sections of this chapter (Table 3). Clinical trials are needed to demonstrate whether any of those new therapies are safe and efficacious in APS patients [98,[100][101][102][103][163][164][165][166][167].…”
Section: Current and Potential New Treatments For Aps-associated Clinmentioning
confidence: 99%